2020
DOI: 10.3390/w12092401
|View full text |Cite
|
Sign up to set email alerts
|

Bed Roughness Effects on the Turbulence Characteristics of Flows through Emergent Rigid Vegetation

Abstract: During floods, the riparian vegetation in a watercourse significantly changes the velocity distribution and the turbulence structures of the flow. However, a certain influence on them is always exerted by the bed sediments. The aim of the present work is to study the bed roughness effects on the turbulence characteristics in an open-channel flow with rigid and emergent vegetation. Toward this end, an experimental campaign was conducted and consisted of three runs with different bed roughness conditions. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 59 publications
4
30
0
Order By: Relevance
“…Experimental studies of velocity profiles, like those shown in Figures 3-5, are of much interest; in some cases also the shear stress profiles are studied by means of velocity fluctuant components and Reynolds stress theory [19,[107][108][109][110][111].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of velocity profiles, like those shown in Figures 3-5, are of much interest; in some cases also the shear stress profiles are studied by means of velocity fluctuant components and Reynolds stress theory [19,[107][108][109][110][111].…”
Section: Methodsmentioning
confidence: 99%
“…The author gives, for every class of channels, the minimum, average, and maximum values of Manning n coefficient, warning that when the channel is artificial, the average values should be used in case of good maintenance only. In Tables 5 and 6 of Chow's book ( [47], p. [110][111][112][113], one can observe that the Manning coefficient is 0.018 sm −1/3 in case of the excavated channel, straight, clean, uniform cross-section with no vegetation, and 0.035 sm −1/3 in case of dense weeds. In natural streams, its values are 0.030 sm −1/3 when the cross-section is clean, and 0.045 sm −1/3 in case of weeds.…”
Section: Descriptive and Photographic Comparison Approachesmentioning
confidence: 99%
“…Recently, Penna et al [18] analyzed the flow field, the turbulent kinetic energy (TKE), and the energy spectra of velocity fluctuations around a rigid stem on three different rough beds. They showed that, in the region below the free surface region, the flow is strongly influenced by the vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…The second review paper [11] deals with the environmental impacts associated with the rapidly growing mariculture industry, while one research paper [12] investigated the flow and concentration patterns downstream an aquaculture cage net panel in parametric flume experiments. Four studies approached the stream and river systems from a variety of perspectives, ranging from the physical modelling of flow with vegetation [13] and the numerical simulation of solute transport in river with dead zones [14], to the laboratory study of flood discharge atomisation [15] and the geomorphic characterisation and classification of a large river [16]. Three contributions are about hyporheic fluxes: two field studies investigated these fluxes at a small river confluence [17] and the effects of such fluxes on the macroinvertebrate community [18], while their relationship with the bioturbation activity of macroinvertebrates was studied in laboratory [19].…”
mentioning
confidence: 99%
“…While studies focused on the flow-plant interaction were mostly performed on smooth channel beds, natural riverbeds are characterised by other roughness elements that also affect flow turbulent structures. As such, Penna et al [13] performed an experimental study on the bed roughness effects on the turbulence characteristics in an open-channel flow with rigid emergent vegetation. The results showed that the flow was strongly influenced by the vegetation in the intermediate layer below the free surface and was affected by a combined effect of vegetation and bed roughness in the near bed layer.…”
mentioning
confidence: 99%